Temporal Summation of Pain Characterizes Women but not Men with Temporomandibular Disorders - Sarlani, Eleni (J Orofac Pain, 2007)
AIMS: To examine differences in temporal summation of mechanically evoked pain between women and men suffering from chronic pain associated with temporomandibular disorders (TMD), as well as between male TMD patients and healthy controls. METHODS: Series of 10 repetitive, mildly noxious mechanical stimuli were applied to the fingers of 27 female TMD patients, 16 male TMD patients, and 20 healthy men. The subjects rated the pain intensity caused by the 1st, 5th, and 10th stimulus in the series. Pain ratings were analyzed by 3-way repeated-measures analysis of variance. RESULTS: Pain ratings increased significantly with stimulus repetition for the female TMD patients (P < .001). Women with TMD exhibited significantly greater temporal summation of pain than TMD men (P < .001). Neither the healthy men nor the male TMD patients exhibited significant increases in pain perception with repetitive stimulation. In the female TMD patient group, perceptual pain magnitudes were higher with an interstimulus interval of 2 seconds rather than 10 seconds (P < .005). CONCLUSION: These findings suggest that central nociceptive processing upregulation is likely to contribute to TMD pain for women but is not a factor for men with TMD.